2017 18th IEEE International Conference on Mobile Data Management (MDM) 2017
DOI: 10.1109/mdm.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Step detection algorithm for accurate distance estimation using dynamic step length

Abstract: In this paper, a new Smartphone sensor based algorithm is proposed to detect accurate distance estimation. The algorithm consists of two phases; the first phase is for detecting the peaks from the Smartphone accelerometer sensor. The other one is for detecting the step length which varies from step to step. The proposed algorithm is tested and implemented in real environment and it showed promising results. Unlike the conventional approaches, the error of the proposed algorithm is fixed and is not affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 9 publications
(15 reference statements)
0
26
0
1
Order By: Relevance
“…Conventional step detector algorithms use accelerometer sensor data to detect steps. Ahmad et al [31] studied the fundamental analysis of stepdetection algorithms and discussed their performance based on dynamic step lengths. Ho et al [32] reported an adaptive step length estimator.…”
Section: Related Workmentioning
confidence: 99%
“…Conventional step detector algorithms use accelerometer sensor data to detect steps. Ahmad et al [31] studied the fundamental analysis of stepdetection algorithms and discussed their performance based on dynamic step lengths. Ho et al [32] reported an adaptive step length estimator.…”
Section: Related Workmentioning
confidence: 99%
“…It integrated the acceleration experienced in three coordinate axes to give an overall acceleration. A Python program was developed to calculate the number of steps and walking speed from the accelerometer's raw data [22,23]. More detailed description is available in the supplementary material [see Additional file 1].…”
Section: Final Devicementioning
confidence: 99%
“…The algorithm's parameters have been optimized and applied to measured data from three different volunteers holding the smartphone at different positions. A new algorithm based on the smartphone sensor has been proposed in [11] to estimate the traveled distance by walking accurately. The algorithm counts the number of peaks in the measured signal by the smartphone's accelerometer.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, Acceleration values will be determined like human walking or running regardless of the accelerometer's orientation. The overall acceleration value is calculated as the square root of three acceleration values, as expressed by equation(2) as in[11].…”
mentioning
confidence: 99%